2018
DOI: 10.1177/0162353218781753
|View full text |Cite
|
Sign up to set email alerts
|

Do High-Achieving Students Benefit From Honors College Participation? A Look at Student Engagement for First-Year Students and Seniors

Abstract: This study investigates findings from the National Survey of Student Engagement (NSSE), comparing various aspects of student engagement between honors college and general education students. Responses from 1,339 honors college students and 7,191 general education students across 15 different universities suggest a positive impact for honors college participation on reflective and integrative learning, use of learning strategies, collaborative learning, diverse discussions, student-faculty interaction, and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The significant findings corroborate previous research focusing on student engagement and honors colleges from the perspective of the students. Miller and Dumford (2018) found evidence that first-year honors students were more likely to engage in the use of learning strategies, collaborative learning, and student–faculty interaction, while senior honors students were also more likely to engage in student–faculty interaction as compared with their general education counterparts. In terms of the DMGT (Gagné, 2009), these findings are consistent with the role of the environmental factor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The significant findings corroborate previous research focusing on student engagement and honors colleges from the perspective of the students. Miller and Dumford (2018) found evidence that first-year honors students were more likely to engage in the use of learning strategies, collaborative learning, and student–faculty interaction, while senior honors students were also more likely to engage in student–faculty interaction as compared with their general education counterparts. In terms of the DMGT (Gagné, 2009), these findings are consistent with the role of the environmental factor.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research suggests that honors students are more likely to be engaged in some, but not all, aspects of the college experience, and that these patterns can differ by class level (Miller & Dumford, 2018). However, it is also important to consider whether honors programs are having an impact on student engagement from the perspective of another vital institutional group: faculty.…”
Section: The Current Studymentioning
confidence: 99%
“…Recent research suggests that honors students are more likely to be engaged in some, but not all, aspects of the college experience, and that these patterns can differ by class level (Miller & Dumford, 2018). However, is also important to consider whether honors programs are having an impact on effective educational practices from the perspective of another vital institutional group: faculty.…”
Section: The Current Studymentioning
confidence: 99%
“…The majority of honors students aspire to earn a doctoral degree (Rinn, 2005). A study conducted by Miller and Dumford (2018) showed that participation in an honors college has a positive effect on several aspects of student engagement, including reflective and integrative learning, collaborative learning, diverse discussions, and student–faculty interaction.…”
Section: Review Of Literaturementioning
confidence: 99%